2020
DOI: 10.1103/physrevb.102.085148
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the unoccupied state dispersions in Ta2NiSe5 with resonant inelastic x-ray scattering

Abstract: The transition metal chalcogenide Ta 2 NiSe 5 undergoes a second-order phase transition at T c = 328 K involving a small lattice distortion. Below T c , a band gap at the center of its Brillouin zone increases up to about 0.35 eV. In this work, we study the electronic structure of Ta 2 NiSe 5 in its low-temperature semiconducting phase, using resonant inelastic x-ray scattering (RIXS) at the Ni L 3 edge. In addition to a weak fluorescence response, we observe a collection of intense Raman-like peaks that we at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 51 publications
(89 reference statements)
1
11
0
Order By: Relevance
“…3 Mapping of the occupied and unoccupied electronic states ). The DFT calculations taken from [66] are superimposed on the experimental data.…”
Section: Time-and Angle-resolved One-and Two-photon Photoelectron Spe...mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Mapping of the occupied and unoccupied electronic states ). The DFT calculations taken from [66] are superimposed on the experimental data.…”
Section: Time-and Angle-resolved One-and Two-photon Photoelectron Spe...mentioning
confidence: 99%
“…By combining one-and two-photon photoelectron spectroscopy, we initially obtain momentum-resolved mapping of the occupied and unoccupied electronic band structure of the low-temperature phase of Ta 2 NiSe 5 , and compare it with density-functional-theory (DFT) calculations [66] (see Section 3). We then look at the photoexcited low-temperature EI phase without driving the transition.…”
Section: Introductionmentioning
confidence: 99%
“…This characteristic mix- ture of localized/itinerant electronic states may lead to a spectrum of partial excitations, where the emission stage of the coherent RIXS process is only active from the d x 2 −y 2 state, which forms a sharp peak in the occupied density of states 16 . In this case, other pathways would be expected to be dominated by incoherent decay channels between broad, itinerant bands resulting in an unresolvable continuum of particle-hole excitations 64,65 . Such a contribution is potentially evidenced by the reduction of quasi-elastic spectral weight in the RIXS spectrum of VO 2 when crossing the MIT 3 which is concomitant with an enhanced d x 2 −y 2 orbital polarization 66 .…”
Section: B Comparison Among Metallic States In Rutile Oxidesmentioning
confidence: 99%
“…Thus, RIXS may be used to probe the particle-hole excitations in momentum space across the band gap between occupied and unoccupied bands near the Fermi energy, whose gap structure closely relates to that of the JDOS. Interestingly, a recent Ni L 3 -edge RIXS study of Ta 2 NiSe 5 [33] in the low temperature phase has demonstrated the resemblance of RIXS spectrum to the JDOS between the occupied valence and unoccupied conduction bands. In fact, since Ni L 3 -edge RIXS specifically involves transition on Ni ions, the spectrum should be related closely to the JDOS projected on the Ni-orbital character.…”
Section: Introductionmentioning
confidence: 99%